Pengaruh Financial Distress, Audit Tenure dan Komisaris Independen Terhadap Integritas Laporan Keuangan dengan Kualitas Audit Sebagai Variabel Moderasi - Farah Nur Azizah; Hermi Hermi; Firdayetti Firdayetti (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study was to test, analyze, and prove the results of the influence of financial distress, audit tenure and independent commissioners on the integrity of financial reports with audit quality as a moderating variable. The data used is secondary data obtained from annual and financial reports. The sample selection was carried out by purposive sampling technique. The sample used in this research is 17 companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research uses moderation regression analysis with panel data. The analytical tool used for testing the hypothesis uses e-views version 9. The results of this study indicate that financial distress and independent commissioners have no significant effect on the integrity of financial statements. However, tenure audits have a significant effect on the integrity of financial statements. Furthermore, moderation of audit quality does not significantly strengthen the effect of financial distress, audit tenure on the integrity of financial statements. The variable that is strengthened by audit quality is the influence of independent commissioners on the integrity of financial statements